Identification of the Bisabolol Synthase in the Endangered Candeia Tree (Eremanthus erythropappus (DC) McLeisch) - Alves Gomes Albertti, Leticia; Delatte, Thierry L.; Souza de Farias, Katyuce; Galdi Boaretto, Amanda; Verstappen, Francel; van Houwelingen, Adele; Cankar, Katarina; Carollo, Carlos Alexandre; Bouwmeester, Harro J.; Beekwilder, Jules (Frontiers in Plant Science, 2018)
Candeia (Eremanthus erythropappus (DC) McLeisch, Asteraceae) is a Brazilian tree, mainly occurring in the cerrado areas. From ethnobotanical information its essential oil is known to have wound healing and nociceptive properties. These properties are ascribed to result from a sesquiterpene alcohol, (−)-α-bisabolol, which is present at high concentrations in this oil. Bisabolol is highly valued by the cosmetic industry because of its antibacterial, anti-inflammatory, skin-smoothing and wound healing properties. Over the past decades, Candeia timber has been collected at large scale for bisabolol extraction from wild reserves and the species is thereby at risk of extinction. To support the development of breeding and nursing practices that would facilitate sustainable cultivation of Candeia, we identified a terpene synthase gene, EeBOS1, that appears to control biosynthesis (−)-α-bisabolol in the plant. Expression of this gene in E. coli showed that EeBOS1 protein is capable of producing (−)-α-bisabolol from farnesyl pyrophosphate in vitro. Analysis of gene expression in different tissues from Candeia plants in different life stages showed a high correlation of EeBOS1 expression and accumulation of (−)-α-bisabolol. This work is the first step to unravel the pathway towards (−)-α-bisabolol in Candeia, and in the further study of the control of (−)-α-bisabolol production.